Financial regimes, financialization patterns and industrial performances: Preliminary remarks - Giovanni Dosi; Valerie Revest; Alessandro Sapio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
The evolutionary taxonomy of financial systems, outlined by Dosi (1990), argued that market-based systems would be comparatively more engaged in the exploration of new technological paradigms, as an outcome of market selective pressure, whereas the more institutionalized finance allocation in credit-based systems would give them an advantage in cumulative learning. This article offers a preliminary assessment of those conjectures in light of the institutional change associated with the financialization process and the "maximizing shareholders value" principle. The available evidence suggests that financialization has de-linked the performance of firms on the financial markets from the determinants of firm-level growth and innovation. Selection among companies increasingly occurs on financial markets, along criteria of short-term returns. As such, financialization has contributed to compress and somewhat degrade the specific properties of the finance-innovation nexus of both financial system archetypes, deteriorating both static and Schumpeterian efficiency.
Keywords: B52; G2; G3; L2; O3; 330; Evolutionary Theory; Financial Systems; Firm growth; Innovation; Financialization